Phenomenal effect of body mass index on VO2max in medical students - Pandit, Rajan (Asian Journal of Medical Sciences, 2017)
Background: Decrease in VO2max and/or increase in body mass index can be used as early marker for the alteration of cardiovascular physiology. Still, the debate over fat or fit for the early predictor of cardiovascular disease risk factor exists. Aims and Objective: The present study was carried out to evaluate the effect of body mass index on VO2max. Materials and Methods: Sixteen female students, group I, normal weight (n=16) and group II, overweight (n=16) were enrolled as participants. The Queen’s College step test was performed on a stool of 16.25 inches (or 41.3 cm) height for a total duration of 3 min at the rate of 22 cycles/min set by a metronome. Results: The average age, BMI, VO2max and sleep duration for normal weight and overweight female participants were 19.25±0.73 years vs 19.43±0.92 years, 20.87±1.17 kg/m2 vs 26.1±0.31 kg/m2; 36.98±0.76 ml/kg/min vs 36.55±0.78 ml/kg/min; 7.81±0.53 hours/day vs 6.23±0.16 hours/day respectively. Conclusion: The relative lower value of aerobic capacity (VO2max) in overweight female as compared to normal weight females may not be an indicator of cardio-respiratory dysfunction, and it is imperative not to make the early extrapolation that all overweight individuals suffer from cardio-respiratory dysfunction and are physically unfit. Asian Journal of Medical Sciences Vol.8(5) 2017 80-82